Abduction and Seduction, Farewells and Reunions: Rinaldo and Armida Between Painting and Opera (Altre Modernità, 2025)
Rinaldo and Armida are two of the main characters in Torquato Tasso’s masterpiece Gerusalemme liberata. It is therefore not surprising that they achieved great success in two other art forms, in addition to literature: painting and opera. From the 16th to the 19th century, the representation of the tragic and sensual love story between the crusader Rinaldo and the sorceress Armida aroused great interest among many painters and librettists. Through an investigation of the octaves recounting their love story, this essay aims to provide some preliminary descriptive and quantitative data on the elements that – during the transition from the Liberata to painting and opera – were accepted, rejected, or modified by artists and librettists.
Keywords: Renaissance; Renaissance Literature; Torquato Tasso; Gerusalemme liberata; Rinaldo and Armida